Electroreduction of CO2 to Formate with Low Overpotential using Cobalt Pyridine Thiolate Complexes. (13th August 2020) - Dey, Subal; Todorova, Tanya K.; Fontecave, Marc; Mougel, Victor
Abstract: Electrocatalytic CO2 reduction to value‐added products provides a viable alternative to the use of carbon sources derived from fossil fuels. Carrying out these transformations at reasonable energetic costs, for example, with low overpotential, remains a challenge. Molecular catalysts allow fine control of activity and selectivity via tuning of their coordination sphere and ligand set. Herein we investigate a series of cobalt(III) pyridine‐thiolate complexes as electrocatalysts for CO2 reduction. The effect of the ligands and proton sources on activity was examined. We identified bipyridine bis(2‐pyridinethiolato) cobalt(III) hexaflurophosphate as a highly selective catalyst for formate production operating at a low overpotential of 110 mV with a turnover frequency (TOF) of 10 s −1 . Electrokinetic analysis coupled with density functional theory (DFT) computations established the mechanistic pathway, highlighting the role of metal hydride intermediates. The catalysts deactivate via the formation of stable cobalt carbonyl complexes, but the active species could be regenerated upon oxidation and release of coordinated CO ligands. Abstract : Molecular cobalt‐based CO2 electroreduction catalysts achieved the conversion of CO2 into HCOOH as the major product with very low overpotential by tuning the electronic properties of the metal centers using pyridine‐thiolate ligands. Formation of a stable carbonyl complex caused deactivation. The active catalyst is regenerate by re‐oxidation, promoting CO ligand release.